Knapps Narrows Calcareous Nannofossil Biozonation over ETM2 and H2 - William Rush; Jean Self-Trail; Yang Zhang; Appy Sluijs; Henk Brinkhuis; James C Zachos; James G Ogg; Marci M Robinson (PANGAEA, 2023)
The Knapps Narrows core was drilled at 38.72129N, -76.33162W on the Eastern Shore of Maryland. The cored target interval lies between 84-102 meters in the Nanjemoy Formation. Calcareous nannofossil biozonation was established in conjunction with paleomagnetic data, allowing us to date the interval to approximately 53.7 mya. Benthic foraminiferal and bulk carbon isotope data allowed for further refinement of the dating of this interval, allowing us to identify ETM2 and H2 on the basis of carbon isotope stratigraphy. For analyses of benthic foraminifera 4-6 Anomalinoides acutus specimens were picked from the 180-250 μm size fraction at each interval. Dinoflagellate cyst assemblages were counted in order to allow for paleo-environmental analysis. Benthic foraminiferal δ18O and TEX86 temperature proxies were compiled over the interval of interest. Semi-quantitative clay mineral assemblages were used to test for changes in the weathering response over hyperthermal intervals. There is excellent agreement between the δ18O and TEX86 temperature proxies, although the highest temperatures do not correspond to either hyperthermal event. There is a noticeable increase in illite content during the ETM2 interval, and an absence of kaolinite. Dinoflagellate assemblages suggest changes in marine paleo-environmental conditions were driven by long-term trends rather than immediate responses to the hyperthermal events.